(untitled) (AI Governance and Society Journal p-ISSN 3117-6097 and e-ISSN 3117-6100, 2025)
Human-in-the-loop (HITL) architectures – system designs that structurally incorporate human judgement, oversight, and intervention within AI decision processes – are widely advocated as a primary mechanism for responsible AI governance. However, the term encompasses a heterogeneous range of architectural patterns, from nominal human involvement that provides no meaningful oversight to deeply integrated collaborative decision-making that genuinely distributes authority between human and AI. This paper develops a comprehensive taxonomy of eight HITL architectural patterns organised across two dimensions – intervention depth (monitoring, advisory, approval, co-decision) and intervention timing (pre-decision, in-decision, post-decision) – and evaluates their governance effectiveness through a mixed-methods study involving expert assessment and a longitudinal analysis of 26 operational AI systems with documented HITL implementations. Expert consensus (n = 36, Kendall W = 0.77) identifies co-decision and approval-tier patterns as most effective for responsible AI governance in high-stakes contexts. Longitudinal analysis demonstrates that HITL implementation depth is significantly associated with reduced governance incidents: deep HITL systems (co-decision or approval tier) exhibit 44.6% fewer governance incidents than shallow HITL systems (monitoring or advisory tier) over a 12-month observation period (IRR = 0.55, 95% CI: 0.44-0.70, p < 0.001). Critically, nominal HITL implementations – those providing human involvement without meaningful oversight authority – show no statistically significant governance benefit compared to fully automated systems. The study contributes a validated HITL taxonomy, a HITL Governance Effectiveness Scale, and design principles for meaningful rather than nominal human oversight.